A systematic review on the effectiveness of eyewear in reducing the incidence and severity of eye injuries in racket sports - Mazarelo, J. F. D.; Winter, S. L.; Fong, D. T. P. (The Physician and Sportsmedicine, 2024)
Purpose To assess what eyewear (if any) reduces eye injury incidence and severity in squash, racketball, tennis and badminton.